2015
DOI: 10.1017/sjp.2015.5
|View full text |Cite
|
Sign up to set email alerts
|

Portuguese Validation of the Consideration of Future Consequences Scale

Abstract: The Consideration of Future Consequences Scale (CFC-S) is a measure of the extent to which individuals reflect and are influenced by the immediate as well as by the distant outcomes of current behavior. It's composed by 12 items, grouped into two subscales (future and immediate). This study aims to explore the factor structure, psychometric properties and construct validity of the Portuguese version of the CFC-S in 5 samples, composed by 527 participants with ages between 13 and 71. A 2 factor structure has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
10

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 30 publications
3
7
0
10
Order By: Relevance
“…Esto demuestra la validez inter-cultural de esta solución bi-factorial primero encontrada en Estados Unidos (Joireman et al, 2008) y que también se ha presentado en una muestra de Portugal (Vásquez Echeverría et al, 2015). Con esta nueva evidencia, consideramos que la utilización de dos factores en el estudio de la relación de la CFC con otros constructos refina enormemente la interpretación que se hacen de los datos.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Esto demuestra la validez inter-cultural de esta solución bi-factorial primero encontrada en Estados Unidos (Joireman et al, 2008) y que también se ha presentado en una muestra de Portugal (Vásquez Echeverría et al, 2015). Con esta nueva evidencia, consideramos que la utilización de dos factores en el estudio de la relación de la CFC con otros constructos refina enormemente la interpretación que se hacen de los datos.…”
Section: Discussionunclassified
“…Como ya fue mencionado, Strathman et al (1994) y muchos otros investigadores que utilizaron la escala, han tratado el constructo de forma unidimensional (recodificando los ítems inmediatos y combinándolos con los futuros). Sin embargo, muchos estudios recientes cuestionan esta solución uni-factorial (Joireman et al, 2008;Petrocelli, 2003;Toepoel, 2010;Vásquez Echeverría, Esteves, Gomes, & Ortuño, 2015;ver, en cambio Hevey et al, 2010), sugiriendo una estructura de dos factores, donde el primero refleja la preferencia por las consecuencias inmediatas de las acciones (CFC-Inmediato) y el otro, las consecuencias más distantes (CFCFuturo). Esta división entre estos dos niveles de futuro, permite hacer un análisis más pormenorizado de los constructos estudiados y afinar la interpretación teórica de los datos (Joireman et al, 2012;Milfont & Schwarzenthal, 2014).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The psychometric properties of the CFC have mainly been examined within the United States, though a validation study was recently conducted in Portugal (Echeverría, Esteves, Gomes, & Ortuño, ). These findings suggest support for the two‐factor model, although the item, “My convenience is a big factor in the decisions I make or the actions I take,” was eliminated to improve model fit and reliability.…”
Section: Future Time Perspective Scalesmentioning
confidence: 99%
“…Strathman et al (1994) reported exploratory and confirmatory factor analyses supporting the idea of a single underlying factor. However, research carried out later suggests that the scale comprises two factors (Joireman, Balliet, Sprott, Spangenberg, & Schultz, 2008;Petrocelli, 2003;Vásquez, Esteves, Gomes, & Ortuño, 2015). For instance, Joireman et al (2008) explored the validity of the two-factor solution.…”
mentioning
confidence: 99%